2020
DOI: 10.1097/lgt.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Tumor Markers in Vulvar Carcinoma Through Extensive Human Papillomavirus DNA Characterization Using Next Generation Sequencing Method

Abstract: Objectives A subset of vulvar carcinomas (VC) are associated with human papillomavirus (HPV) DNA. This trait can be used to identify tumor markers for patient's follow-up. A large diversity of HPV prevalence in VC has been reported, but no data are available concerning the insertional HPV status in this tumor type. Therefore, we have used an innovative next generation sequencing (NGS)-based CaptHPV method able to provide an extensive characterization of HPV DNA in tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“… 33 HPV integration in TP63 genes was recently reported in HPV-positive vulvar cancer patients. 34 In another HPV-positive head and neck squamous cell carcinoma study, HPV sites of integration into MIPOL1/TTC6 were identified in more than one tumour sample. The integration of HPV into the ERBB2 gene site was observed in two patients in association with ERBB2 amplifications, in concordance with previous reports.…”
Section: Discussionmentioning
confidence: 96%
“… 33 HPV integration in TP63 genes was recently reported in HPV-positive vulvar cancer patients. 34 In another HPV-positive head and neck squamous cell carcinoma study, HPV sites of integration into MIPOL1/TTC6 were identified in more than one tumour sample. The integration of HPV into the ERBB2 gene site was observed in two patients in association with ERBB2 amplifications, in concordance with previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…In the primary GWAS analysis, the T allele of the intronic rs79048288 variant within CCDC148 was associated with a 4.4-fold higher AIMSS risk and the G allele of the intergenic rs912571 upstream of PPP1R14C was associated with a 3.3-fold lower AIMSS risk. In silico analyses did not reveal any obvious functional impact of the intronic variant within CCDC148 (rs79048288), and little is known about the physiological function of this protein, except that dysregulated expression has been reported in several cancer types 38,39 . In silico analyses revealed that the G allele of rs912571 was associated with higher expression of PPP1R14C in sun-exposed skin, indicating that this variant could be functionally consequential.…”
Section: Discussionmentioning
confidence: 99%
“…本例除 EML4 - ALK 外同时存在其他 ALK 融合基因( CCDC148 - ALK 、 PKDCC - ALK 和 VIT - ALK )。截至目前,已经发现了许多非 EML4 的 ALK 融合伴侣 [ 4 ] 。有文献报道, VIT - ALK 是对阿来替尼敏感的融合基因, PKDCC - ALK 融合是对 ALK -TKI WX-0593敏感的融合基因 [ 30 - 31 ] 。本例报道NSCLC患者中存在 CCDC148 - ALK 融合,一般 CCDC148 与妇科肿瘤相关 [ 32 ] 。本文资料中,NSCLC患者在阿来替尼治疗期间 CCDC148 - ALK 显著清除,推测 CCDC148 - ALK 可能是对阿来替尼敏感的融合基因,但仍须进一步研究证明。…”
Section: 讨论unclassified